Study on the current situation as well as countermeasures for music education at rural primary and middle schools in Shaanxi, China - Fan, Qi (Penerbit Universiti Kebangsaan Malaysia, 2022)
Music education is an important means of quality education and plays an irreplaceable role in inducing all-round development of students. China’s rural areas are weak areas for popularization of education. Music is a scarce subject in rural schools, but it is not a dispensable subject. Rural students should receive strict and formal education. Music education is important for cultivating students’physical and mental health and healthy thinking. The influences and feelings produced by, aesthetic taste, etc. cannot be replaced by other disciplines of education. Currently, music education in rural primary and secondary schools in Shaanxi province, China is restricted by various factors while still being far from achieving requirements of modern education. This research aims to study, investigate and analyse the current situation of music education in rural areas, highlight the problems in music education in rural area as well as proposing related solutions to promote the development of music education in rural Shaanxi province in China. To solve the problems of music education in rural primary and secondary schools in Shaanxi, it is necessary to increase the importance of leadership to music education in rural primary and secondary schools in Shaanxi, increase investment in music education in rural primary and secondary schools in Shaanxi, and innovate the training and supply mechanism of music teachers in rural primary and secondary schools in Shaanxi.